Comparative evaluation of serum cotinine levels in chronic periodontitis and chronic obstructive pulmonary disease - Madhurya Nagaraj Kedlaya; Amitha Ramesh; Giridhar Belur Hosmane; Rahul Bhandary; Hakkim Rajula Sajna; Biju Thomas (Wolters Kluwer Medknow Publications, 2021)
Context: Periodontitis and chronic obstructive pulmonary disease (COPD) are chronic progressive inflammatory conditions. Smoking has been associated with both chronic periodontitis and COPD. Hence, the present study was designed to correlate serum levels of cotinine with the severity of periodontal disease with or without COPD. Settings and Design: A total of eighty patients, twenty healthy individuals, twenty patients with chronic generalized periodontitis without smoking and without COPD, twenty patients who are smokers with chronic periodontitis without COPD and twenty patients who are smokers with chronic periodontitis and COPD in the age range of 43-65 years were selected for the study. Subjects and Methods: Serum cotinine level assessment, smoking history, and periodontal examination were done in all the patients and the data obtained were statistically analyzed. Results: The mean serum cotinine level was highest in smokers with chronic periodontitis and COPD (93.642 ± 14.727) and it differed significantly between the four groups (P < 0.001). There is a significant positive correlation between the number of cigarettes and serum cotinine levels in both groups involving smoking. There was no significant correlation between serum cotinine level and clinical attachment loss in chronic periodontitis smokers with or without COPD. Conclusions: The result of this study indicates that increased smoking with COPD causes a higher chance of progression of periodontal destruction but it is not statistically significant. Furthermore, this study indicates that the assessment of serum cotinine levels is a reliable method to evaluate smoking exposure.